Probabilistic Traveling Salesman Problem and Harmony Search Algorithms in Pharmacy Supply Optimization - Twaróg, Sebastian; Szołtysek, Jacek; Szwarc, Krzysztof; Boryczka, Urszula (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
This paper demonstrates the utilitarian significance of the Probabilistic Traveling Salesman Problem (PTSP) in planning travel routes by companies which provide distribution services for pharmacies, with a particular consideration of variable customer demand. The optimization problem was solved using the Harmony Search (HS) algorithm, thus verifying its utility based on one real instance of PTSP (representing the problem of pharmacy supply reliability) and three tasks from the public TSPLIB library (adjusted to PTSP). As a result of the conducted research, significant utility of the hybrid approach was identified, assuming the combination of HS with popular 2‑opt method, which enabled achievement of good results within acceptable period (in practical applications).